2016
DOI: 10.1515/jpem-2015-0453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left and right ventricular functions using conventional and tissue Doppler echocardiography in children with type 1 diabetes mellitus

Abstract: Conventional and TDI echocardiography revealed impairment in left ventricular functions in some patients. Tissue Doppler echocardiography also revealed diastolic impairment in some patients who appeared normal with PW Doppler echocardiography. The present study found that impairment in left ventricular diastolic functions is directly related to glycemic control and the rate of diabetic cardiomyopathy was higher in children with poor metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The PW Tei index, a parameter computed from cardiac time intervals, seems to be an attractive method to assess cardiac function because it is relatively unaffected by anatomical disturbances or localized abnormalities of myocardium …”
Section: Discussionmentioning
confidence: 99%
“…The PW Tei index, a parameter computed from cardiac time intervals, seems to be an attractive method to assess cardiac function because it is relatively unaffected by anatomical disturbances or localized abnormalities of myocardium …”
Section: Discussionmentioning
confidence: 99%
“…Tissue Doppler, atleast for some variables, is thought to be superior for assessing cardiac function compared with conventional echocardiography; however, the method is associated with some potential limitations as the results are sensitive to probe angle and noise interference and are associated with intraobserver and interobserver variability. [46][47][48] To evaluate the reproducibility and accuracy of the measurements, we therefore assessed intraobserver and interobserver variability and found the variabilities to be within an acceptable range. The women participating in this study were likely more healthy than women in general and not representative of all female populations.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…In children and adolescents with T1DM, studies showed variable results on subclinical LV diastolic dysfunction using conventional echocardiographic parameters or tissue Doppler . Also, tissue Doppler imaging studies have demonstrated subclinical systolic longitudinal dysfunction in adult and children patients with T1DM …”
Section: Introductionmentioning
confidence: 99%